Sociocultural Determinants and Patterns of Healthcare Utilization for Epilepsy Care in Uganda - Koltai, Deborah C.; Dunn, Timothy W.; Smith, Patrick J.; Sinha, Drishti D.; Bobholz, Samuel; Kaddumukasa, Mark; Mwesige, Angelina Kakooza; Kajumba, Mayanja; Smith, Caleigh E.; Kaddumukasa, Martin N.; Teuwen, Dirk E.; Nakasujja, Noeline; et al. (Epilepsy & Behavior, 2021)
Epilepsy is a global public health concern, with the majority of cases occurring in lower- and middle-income countries where the treatment gap remains formidable. In this study, we simultaneously explore how beliefs about epilepsy causation, perceived barriers to care, seizure disorder characteristics, and demographics influence the initial choice of healthcare for epilepsy and its impact on attaining biomedical care (BMC).This study utilized the baseline sample (n = 626) from a prospective cohort study of people with epilepsy (PWE) attending three public hospitals in Uganda (Mulago National Referral Hospital, Butabika National Referral Mental Hospital, and Mbarara Regional Referral Hospital) for epilepsy care. Patient and household demographics, clinical seizure disorder characteristics, and sociocultural questionnaires were administered. Logistic regression and principal component analyses (PCA) were conducted to examine associations with the choice of primary seizure treatment.The sample was 49% female, and 24% lived in rural settings. A biomedical health facility was the first point of care for 355 (56.7%) participants, while 229 (36.6%) first sought care from a traditional healer and 42 (6.7%) from a pastoral healer. Preliminary inspection of candidate predictors using relaxed criteria for significance (p < 0.20) identified several factors potentially associated with a greater odds of seeking BMC first. Demographic predictors included older caredriver (decision-maker for the participant) age (odds ratio [OR]: 1.01, 95% confidence interval [CI]: [0.99, 1.02], p-value: 0.09), greater caredriver education level (OR = 1.21, 95% CI: [1.07, 1.37], p-value = 0.003), and lower ratio of sick to healthy family members (OR = 0.77 [0.56, 1.05], P = 0.097). For clinical predictors, none of the proposed predictors associated significantly with seeking BMC first. Self-report causation predictors associated with a greater odds of seeking BMC first included higher belief in biological causes of epilepsy (OR = 1.31 [0.92, 1.88], P = 0.133) and lower belief in socio-spiritual causes of epilepsy (OR = 0.68 [0.56, 0.84], P < 0.001). In the multivariate model, only higher caredriver education (OR = 1.19 [1.04, 1.36], P = 0.009) and lower belief in socio-spiritual causes of epilepsy (OR = 0.69 [0.56, 0.86], P < 0.01) remained as predictors of seeking BMC first. Additionally, PCA revealed a pattern which included high income with low beliefs in nonbiological causes of epilepsy as being associated with seeking BMC first (OR = 1.32 [1.12, 1.55], p = 0.001). Despite reaching some form of care faster, individuals seeking care from traditional or pastoral healers experienced a significant delay to eventual BMC (P < 0.001), with an average delay of more than two years (traditional healer: 2.53 years [1.98, 3.24]; pastoral care: 2.18 [1.21, 3.91]).Coupled with low economic and educational status, belief in spiritual causation of epilepsy is a dominant determinant of opting for traditional or pastoral healing over BMC, regardless of concurrent belief in biological etiologies. There is a prolonged delay to eventual BMC for PWE who begin their treatment seeking with nonallopathic providers, and although nonallopathic healers provide PWE with benefits not provided by BMC, this notable delay likely prevents earlier administration of evidence-based care with known efficacy. Based on these findings, initiatives to increase public awareness of neurobiological causes of epilepsy and effectiveness of biomedical drug treatments may be effective in preventing delays to care, as would programs designed to facilitate cooperation and referral among traditional, faith-based, and biomedical providers.
Keywords: Healthcare seeking, Determinants, Epilepsy, Uganda, Culture